Proofs Satisfy All the Figures which are satisfied with a Statement of a Theorem: A Geometrical Case Study - Chhatkuli, Shyam Bahadur (International Research Journal of MMC, 2022)
The objective of the study is to find the learning effectiveness of given the theorem of geometry of class10 in the book published by government of Nepal MOEST which has been the subject of debate among teachers and learners. The study primarily focus Makawanpur district and the informants were selected convinently for the study. There are 95 community schools and 41 private schools in the district. The teachers were selected from both Nepali and English mediums. I conducted the questionnaire survey of the selected teachers and a case study of students. So, there were 40 mathematic teachers for the data collection and five students. Primary data had been collected visiting personally to fill up a set questionnaire with six objectives yes/no and true/false questions. There was a pilot test before the collection of the data. It was found that the present diagram and used strategy of class 10 book has to be reviewed immediately before the new session starts for the coming academic session. The conclusion of the study is that the debatable proof of theorem can be replaced with the one that matches the principle of theorem “Figures which are satisfied with a statement of a theorem the proofs satisfy all of them”.